Adoption contracts in Оld Uyghur legal documents (AD01-AD03): formulaic structure and legal terminology - Burkitbayeva, Ш.Д.; Yussupova, Д.Б. (Turkic Studies Journal, 2026)
This article provides a comprehensive analysis of three Old Uyghur adoption contracts (AD01-AD03) as examples of family legal documents dating from the thirteenth to fourteenth centuries. The study aims to identify the standard formulaic structure of adoption agreements and to examine the legal terminology that defines the status of the child, property-related provisions, mechanisms that safeguard the validity of the transaction, and procedures for confirming the legal right to adoption. Old Uyghur contracts constitute one of the most informative sources for reconstructing everyday legal norms and social practices. However, the limited number of extant texts concerning adoption necessitates meticulous documentary analysis and careful interpretation. Old Uyghur legal documents reveal the development of the legal vocabulary of the ancient Turkic peoples and enable comparative analysis with the legal terminology of modern Turkic languages, contributing to a deeper understanding of their historical development. The study encompasses two interrelated areas. First, a formal analysis is conducted in which each document is examined and compared with respect to its date, the names of the parties involved, the legal act of adoption, conditions of guardianship and conduct, clauses concerning compensation, prohibitions and sanctions, as well as protocol elements (witnesses, signatures/seals, and scribe’s note). Second, lexemes bearing legal significance are classified according to semantic domains, including ‘status/kinship’, ‘payments and property’, ‘sanctions and legality’ and ‘authentication’. In order to enhance conceptual clarity, a quantitative method was employed: the frequency of legal terms was calculated through individual counts, and their distribution across each document was visually represented. The results of the study demonstrate that documents AD01–AD03 exhibit a consistent formulaic structure. The most significant term is oğulluk (adopted son), which functions as the key legal concept defining both the obligations of the adoptive parent and the legal status of the child as a central component of the transaction. The inclusion of compensation in the form of ‘milk payment’ (süt sevinci) is not obligatory, as some contracts do not contain such a provision. This distinction makes it possible to differentiate adoption from the sale or pledging of a child and to interpret it as a ‘transfer of status’ rather than a ‘commodity transaction’. In the section devoted to sanctions, elements of established and formal legal terminology are employed. Authentication markers such as tanuq, tamga/nişan and bitidim constitute the evidentiary basis of the contract and ensure the legal validity and stability of the newly established status. All surviving documents discussed in this study indicate that only boys were adopted, which can be explained by the inheritance system and the economic role of the ‘son’ within the patrilineal family structure. The scholarly contribution of this study lies in proposing a new descriptive model for Old Uyghur adoption contracts and in systematizing their legal vocabulary for future terminological, comparative, and historical research.